1018 Implementing A Standardised Orthopaedic Admission Pro-Forma to Improve Adherence to The Royal College of Surgeons of England (RCSEng) Best Practice Clerking Guidelines. (4th May 2021) - Peacock, C; North, D; Brookes, T
Abstract: Introduction: Within our Trust, Orthopaedic patients are clerked in on A&E notes via freehand text. Audit, clinical incidents, and root cause analysis revealed suboptimal documentation. Using RCSEng Best Practice Guidelines we designed, implemented, and evaluated the impact of an admission pro-forma on quality of clerking. Method: An Orthopaedic clerking pro-forma was designed based on standards set by RCSEng and feedback from Orthopaedic colleagues. First- and second-cycle data collection involving quantitative analysis of clerking against RCSEng domains was conducted before (n = 23) and after (n = 25) intervention. Fisher's exact test was performed to calculate the statistical significance of our data. A qualitative survey was performed to gain feedback on the pro-forma. Results: Observations, allergies, and smoking history were omitted in over half of freehand documentations. Medical/surgical history and management plans were well documented regardless. Intervention resulted in statistically significant increases in 7 out of 12 RCSEng clerking domains, most notably allergies (p < 0.00001). Qualitative feedback was positive; 100% of those surveyed stated that the pro-forma 'improved quality of clerking' and 'benefited clinical decision making'. Conclusions: Our study demonstrated that implementing an Orthopaedic pro-forma improved adherence to RCSEng best practice clerking guidelines compared to freehand documentation and standardised the process improving the level and quality of documentation.